A New Hope for the Patients of Non‐Alcoholic Steatohepatitis: FDA Gives Green Signal for Resmetirom Use - Abdul Haseeb Hasan; Muhammad Ali Abid; Muhammad Hafi Abid; Laiba Suhail; Abubakar Nazir (Health Science Reports, 2025)
ABSTRACT Background and Aims Non‐Alcoholic Steatohepatitis (NASH), a severe form of Non‐Alcoholic Fatty Liver Disease (NAFLD), is characterized by inflammation and fibrosis in the liver, often progressing to cirrhosis and hepatocellular carcinoma. Despite its rising prevalence and significant disease burden, effective pharmacological treatments have been limited to lifestyle modifications and surgical interventions. Recently, resmetirom, a thyroid hormone receptor‐β agonist, received FDA approval for treating NASH, offering new hope to patients. This review explores the current understanding of NASH and the role of resmetirom as a breakthrough therapeutic option. Methods This study is a comprehensive literature review analyzing peer‐reviewed articles, clinical trial data, and public health reports. No original analyses were conducted, and no statistical software was utilized in this review. Results Resmetirom demonstrated efficacy in resolving NASH without fibrosis progression and improving fibrosis scores in patients with biopsy‐confirmed NASH. In a randomized Phase 3 trial, significant histological improvements were observed in 25.9% and 29.9% of patients receiving 80 and 100 mg doses, respectively, compared to 9.7% in the placebo group. Similar trends were noted in fibrosis improvement, with 24.2% and 25.9% of patients showing ≥ 1 stage improvement compared to 14.2% in the placebo group. Adverse effects, including nausea and diarrhea, were reported more frequently in the treatment groups, but the rates of serious adverse events were comparable across groups. Conclusion The approval of resmetirom marks a significant advancement in the treatment of NASH, addressing the limitations of lifestyle‐based interventions. As the obesity epidemic drives the increasing prevalence of NASH, resmetirom provides a promising therapeutic option, paving the way for improved patient outcomes and future research.